At Westonci.ca, we connect you with the best answers from a community of experienced and knowledgeable individuals. Get accurate and detailed answers to your questions from a dedicated community of experts on our Q&A platform. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.

given f (x) = 2x^2 + 3x - , find f (-1).

Sagot :

Answer:

f(-1)=-1

Step-by-step explanation:

Substitute x=-1 into the function:

f(-1) = 2(-1)^2 + 3(-1) = 2(1) - 3 = 2 - 3 = -1

Therefore, f(-1)=-1